Premature Ventricular Contraction Coupling Interval Variability Destabilizes Cardiac Neuronal and Electrophysiological Control: Insights From Simultaneous Cardioneural Mapping. (April 2017) - Hamon, David; Rajendran, Pradeep S.; Chui, Ray W.; Ajijola, Olujimi A.; Irie, Tadanobu; Talebi, Ramin; Salavatian, Siamak; Vaseghi, Marmar; Bradfield, Jason S.; Armour, J. Andrew; Ardell, Jeffrey L.; Shivkumar, Kalyanam
Abstract : Background—: Variability in premature ventricular contraction (PVC) coupling interval (CI) increases the risk of cardiomyopathy and sudden death. The autonomic nervous system regulates cardiac electrical and mechanical indices, and its dysregulation plays an important role in cardiac disease pathogenesis. The impact of PVCs on the intrinsic cardiac nervous system, a neural network on the heart, remains unknown. The objective was to determine the effect of PVCs and CI on intrinsic cardiac nervous system function in generating cardiac neuronal and electric instability using a novel cardioneural mapping approach. Methods and Results—: In a porcine model (n=8), neuronal activity was recorded from a ventricular ganglion using a microelectrode array, and cardiac electrophysiological mapping was performed. Neurons were functionally classified based on their response to afferent and efferent cardiovascular stimuli, with neurons that responded to both defined as convergent (local reflex processors). Dynamic changes in neuronal activity were then evaluated in response to right ventricular outflow tract PVCs with fixed short, fixed long, and variable CI. PVC delivery elicited a greater neuronal response than all other stimuli ( P <0.001). Compared with fixed short and long CI, PVCs with variable CI had a greater impact on neuronal response ( P <0.05 versus short CI), particularly on convergent neurons ( P <0.05), as well as neurons receiving sympathetic ( P <0.05) and parasympathetic input ( P <0.05). The greatest cardiac electric instability was also observed after variable (short) CI PVCs. Conclusions—: Variable CI PVCs affect critical populations of intrinsic cardiac nervous system neurons and alter cardiac repolarization. These changes may be critical for arrhythmogenesis and remodeling, leading to cardiomyopathy. Abstract : Supplemental Digital Content is available in the text.